2011
DOI: 10.1098/rspa.2011.0153
|View full text |Cite
|
Sign up to set email alerts
|

Maximum-principle-satisfying and positivity-preserving high-order schemes for conservation laws: survey and new developments

Abstract: ), genuinely high-order accurate finite volume and discontinuous Galerkin schemes satisfying a strict maximum principle for scalar conservation laws were developed. The main advantages of such schemes are their provable high-order accuracy and their easiness for generalization to multi-dimensions for arbitrarily high-order schemes on structured and unstructured meshes. The same idea can be used to construct high-order schemes preserving the positivity of certain physical quantities, such as density and pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
266
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(267 citation statements)
references
References 22 publications
1
266
0
Order By: Relevance
“…The flux limiter first detects critical numerical fluxes which may lead to negative density and pressure, then limits these fluxes to satisfy a sufficient condition for preserving positivity. Unlike the approaches in [18,19,20], in which positivity-preserving and the maintenance of high order accuracy are considered simultaneously when designing the limiter, here we design the cut-off flux limiter to satisfy positivity only, and then prove a posteriori the maintenance of high order accuracy under a time step restriction. It appears that, in our numerical experiments, a much less restrictive time-step size condition is sufficient for preserving positivity without destroying overall accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flux limiter first detects critical numerical fluxes which may lead to negative density and pressure, then limits these fluxes to satisfy a sufficient condition for preserving positivity. Unlike the approaches in [18,19,20], in which positivity-preserving and the maintenance of high order accuracy are considered simultaneously when designing the limiter, here we design the cut-off flux limiter to satisfy positivity only, and then prove a posteriori the maintenance of high order accuracy under a time step restriction. It appears that, in our numerical experiments, a much less restrictive time-step size condition is sufficient for preserving positivity without destroying overall accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…For even higher-order conservative schemes, Perthame and Shu [11] proved that, given a first-order positivity-preserving scheme, such as Godunov-type schemes, one can always build a higher-order positivity-preserving finite volume scheme under the following constraints: (a) the cell-face values for the numerical flux calculation have positive density and pressure, (b) additional limits on the interpolation under a more restrictive CFL-like condition. With a different interpretation of these constraints based on certain Gauss-Lobatto quadratures, positivity-preserving methods have been successfully developed for high-order discontinuous Galerkin (DG) methods [18] and weighted essentially non-oscillatory (WENO) finite volume and finite difference schemes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Though remedies have been proposed in cases where the maximum principle is satisfied [Zhang and Shu 2011], these do not directly apply in the case of the two-continua equations. During simulation we allow αw / ∈ [0; 1] as practice has shown that αw remains bounded in the discrete case (section 4), and that clamping αw to [0; 1] results in mass conservation issues.…”
Section: Timementioning
confidence: 99%
“…When it comes to discontinuous methods, most of the shock capturing techniques are based on the concept of slope limiter, proposed by Cockburn and Shu for conservation laws [11,10] and latter adapted to the convection-dominated convection-diffusion problem [12]. The same strategy can be applied to finite volume methods (see [33,34,35]). Again, these methods consist in a postprocess after the solution is computed and are designed for explicit methods.…”
Section: Introductionmentioning
confidence: 99%